Australian teachers' perceptions of effectiveness in a performative culture. (January 2022) - Simpson, Alyson; Day, Christopher; Goulding, James; Asha, Jennifer
Abstract: Teachers' perceptions of effectiveness are shaped by myriad factors, including broad-based national education policy, personal values, and the demands of particular schools and students. Previous research has not investigated the shifting impact of influences across different career phases accounting for cultural differences. This small-scale study addresses that gap. Interviews with Australian primary and secondary teachers analysed through a sociocultural lens revealed positive and negative factors of influence. Our research contributes to international debates by highlighting tensions between 'effectiveness' defined by administrators and policy frameworks, and 'effectiveness' defined by teachers in locally situated, culturally prescribed, and professionally negotiated experience. Highlights: Teacher effectiveness is impacted by personal, situational and policy conditions. Teacher commitment, agency, and professional identity are dynamically related. Influences on teacher effectiveness vary across career phases and contexts. Teacher professionalism is culturally defined and locally negotiated. Contextualised agency supports teacher effectiveness.